Advanced Surface Modification for 3D-Printed Titanium Alloy Implant Interface Functionalization - Sheng, Xiao; Wang, Ao; Wang, Zhonghan; Liu, He; Wang, Jincheng; Li, Chen (Frontiers in Bioengineering and Biotechnology, 2022)
With the development of three-dimensional (3D) printed technology, 3D printed alloy implants, especially titanium alloy, play a critical role in biomedical fields such as orthopedics and dentistry. However, untreated titanium alloy implants always possess a bioinert surface that prevents the interface osseointegration, which is necessary to perform surface modification to enhance its biological functions. In this article, we discuss the principles and processes of chemical, physical, and biological surface modification technologies on 3D printed titanium alloy implants in detail. Furthermore, the challenges on antibacterial, osteogenesis, and mechanical properties of 3D-printed titanium alloy implants by surface modification are summarized. Future research studies, including the combination of multiple modification technologies or the coordination of the structure and composition of the composite coating are also present. This research provides leading-edge functionalization strategies of the 3D printed titanium alloy implants.